Peran Bank Sampah Dalam Meningkatkan Kesadaran Masyarakat Terhadap Pemilahan Sampah - Sulaksono Prabowo, Rachmad; Ade Wahyu Yusariarta P.P; Gusti Umindya N.T.; Karen Feronica Tunggale; Maria Diva Yuniar Sirait; Mochamad Ferdy Nur Prastya (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Community service activities were conducted directly in the RT 07 area of ​​Sungai Merdeka Village, KM.36, Samboja, East Kalimantan. The problem raised in this activity was the garbage scattered in the drainage system around the environment. The amount of waste will cause the environment to become dirty. Often this can cause flooding if the rainfall is high. Therefore, we as the Q2-a group through the ITK community service program tried to conduct socialization and practice of making a waste bank in the area. The results obtained from the waste bank socialization activity include: Increasing public knowledge and insight about the role of waste banks, Increasing public awareness in waste sorting, and Waste management from the results of the waste bank by the community.